RANCANG BANGUN WEBSITE DROPSHIP KOSMETIK MENGGUNAKAN TEKNIK RESTFUL API - Rismawati. S; , Ridwan A. Kambau; Hariani (Prodi Teknik Informatika Universitas Islam Negeri Makassar, 2022)
[COSMETIC DROPSHIP WEBSITE DESIGN USING RESTFUL API TECHNIQUE] Dropshipping is a solution for people who want to start an online business but have limited capital, drop shippers only need to market products from other parties without having to buy them first. One product that is in great demand by the public today is cosmetics which people are willing to spend a lot of money to look perfect, with a cosmetic dropship website can provide opportunities for dropshippers who want to develop their online business using their own name. The purpose of this research is to produce a web-based application for cosmetic dropship products that can assist dropshippers in marketing their product online. The type of research is qualitative research using a design and creation approach which includes website-based design and development . The design used is the waterfall. This system is tested using black-box testing. The results obtained based on questionnaires from 10 dropshipper respondents and 10 respondents to the website obtained an interpretation percentage of 84.6% of dropshipper respondents and 85.4% of buyer respondents. Thus, it can be concluded that this cosmetic dropship website can help and facilitate dropshippers and buyers in selling and buying cosmetic products online.